Kiai Nur Ali's Dakwah Bil-Hal: A Pesantren and Piety-Based Strategy for Community Development - Al-Adawiyah, Rabiah; Abdul Majid, Zamakhsyari (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
This study examines the praxis of dakwah bil-hal (exemplary-based propagation) as employed by Kiai Haji Nur Ali, a charismatic Indonesian Islamic scholar. Moving beyond textual preaching, Kiai Nur Ali’s approach strategically integrated spiritual teachings with tangible socio-economic action, centering the pesantren (Islamic boarding school) as an engine for holistic community development. This qualitative research, utilizing historical and ethnographic analysis, argues that his methodology effectively constructed a sustainable ecosystem of piety (taqwa) and empowerment. By establishing educational institutions, cooperatives, and social programs directly linked to the moral framework of the pesantren, he demonstrated how religious values could drive practical improvements in welfare, education, and communal solidarity. This article concludes that Kiai Nur Ali’s model presents a significant case study of indigenous, faith-based community development, offering insights into the role of traditional religious leadership in addressing modern societal challenges through a framework of integrated spiritual and material progress.